2016
DOI: 10.1021/acs.iecr.5b03475
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Prediction of Vapor–Liquid Equilibrium Using the Peng–Robinson Equation of State and UNIQUAC Activity Coefficient Model

Abstract: Many important processes in the oil and gas industry (e.g., distillation, absorption, extraction) involve contact between liquid and vapor phases. The reliable design of these industrial processes requires accurate thermodynamic models to describe the vapor−liquid equilibrium (VLE) of the mixtures of interest. Two common approaches, γ−ϕ and ϕ−ϕ, are utilized to describe such VLE behavior. In this study, we present a comprehensive assessment of the representation and predictive capability of these two approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…To reduce the parameter correlation and narrow down the range of acceptable values in the NRTL model parameters, two modified NRTL models, mNRTL1 and mNRTL2, were developed in our previous work. 21,22 Equations 8 and 9 present the model parameters for the modified NRTL:…”
Section: Phase Equilibrium Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the parameter correlation and narrow down the range of acceptable values in the NRTL model parameters, two modified NRTL models, mNRTL1 and mNRTL2, were developed in our previous work. 21,22 Equations 8 and 9 present the model parameters for the modified NRTL:…”
Section: Phase Equilibrium Modelsmentioning
confidence: 99%
“…22,23 Further, it was observed that the new proposed parameters, g ij and R ij , are less correlated than the original NRTL parameters a 12 and a 21 . 21,22 The interaction ratio, R ij , in the proposed mNRTL2 model was generalized in terms of pure-fluid properties, acentric factor, and critical pressure, to develop the one-parameter NRTL model (mNRTL1). 3 Pertinent equations and derivatives of the original NRTL and modified NRTL models are presented in the Supporting Information (Appendices A and B).…”
Section: Phase Equilibrium Modelsmentioning
confidence: 99%
“…The former tends to be more frequently applied due to the high dissociation pressures of gas hydrates. 9 While most process simulators use cubic equations of state, activity coefficient models or CPA 10 to describe the fluid phases, some recent studies have also considered some SAFT variants. For the representation of noninhibited hydrates of light gases and hydrocarbons some of these studies include those of Fouad et al 11 and el Meragawi et al 12 with PC-SAFT and that of Waseem and Alsaifi 13 with the SAFT-VR Mie.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, for industrial applications, these fall into two categories: Equations of state or activity coefficient models. The former tends to be more frequently applied due to the high dissociation pressures of gas hydrates …”
Section: Introductionmentioning
confidence: 99%
“…In most industrial software, fluid phases are either described by an equation of state or by an activity coefficient model (or both, using excess Gibbs energy mixing rules). For the case of hydrate calculations, the first is more commonly applied because of the high dissociation pressures involved …”
Section: Introductionmentioning
confidence: 99%